PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PENGAWASAN TERHADAP KINERJA ANGGARAN PADA PEMERINTAH DAERAH KABUPATEN KAMPAR - Wanda Fernandes; Kennedy -; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of Accountability, Transparency and Supervision  on the Performance of Budgetting of Kampar Government. This study was conducted at SKPD of Kampar Regency. The population in this study were employed who worked in the SKPD Kampar Regency (32 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD/ the head of financial, and PPK SKPD. The data used in this study were 60 data. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0. The result of this study indicated that the Accountability, the Transparency and The Supervision has significantly effect on effectiveness of the Performance Budgeting. The magnitude of the effect (R2) the Accountability, the Transparency and Supervision on the effectiveness of the Performance Budgeting area was 23%. While the remaining 77% is influenced by other independent variabel that are not observed in this study.   Keywords: Accountability, Transparency, Supervision, Performance, and Budgeting.